Wedge-cell technique as a simple and effective method for chromatic dispersion determination of liquid crystals - Rutkowska, Katarzyna Agnieszka; Orzechowski, Kamil; Sierakowski, Marek (Photonics Letters of Poland, 2016)
In this letter we present a wedge-cell method and then compare it with other techniques that can be used to determinate refractive indices of liquid crystalline materials. This simple goniometric technique is of particular significance when used for liquid crystalline materials characterized by high refractive indices, for which refractometric methods are approaching their upper limits. Importantly, a measurement technique proposed here requires relatively small amount of a liquid crystalline material and gives appropriate results for different light sources from the wide spectral range, allowing thus for chromatic dispersion curves (in different temperatures) to be obtained. Full Text: PDF References M.O. Ko, S. Kim, J. Kim, B.W. Lee, M.Y. Jeon, "Measurement of Effective Refractive Index of Nematic Liquid Crystal in Fabry-Perot Etalon", J. Opt. Soc. Korea 19, 346 (2015). CrossRef K. Thingujama, S. Sarkara, B. Choudhurya, A. Bhattacharjeea, "Effect of Temperature on the Refractive Indices of Liquid Crystals and Validation of a Modified Four-Parameter Model", Acta Phys. Polonica A 122(4), 754 (2012). CrossRef T.A. El-Dessouki, M. Roushdy, N.I. Hendawy, M.M. Naoum, A.A. Zaki, "Optical Measurements of Thermotropic Liquid Crystals", J. Modern Physics 4, 39 (2013). CrossRef J. Li, S. Wu, S. Brugioni, R. Meucci, S. Faetti, "An Experimental Method for Determination of the Refractive Index of Liquid Samples Using Michelson Interferometer" J. Appl. Phys. 97, 073501 (2005). CrossRef B. Abbas, M.A. Khalil, "An Experimental Method for Determination of the Refractive Index of Liquid Samples Using Michelson Interferometer", Acta Phys. Polonica A 129, 59 (2016). CrossRef S.R. Kachiraju, D. A. Gregory, "Determining the refractive index of liquids using a modified Michelson interferometer", Opt. Laser Techn. 44, 2361 (2012). CrossRef J. Yan, M. Jiao, L. Rao, S. Wu, "Direct measurement of electric-field-induced birefringence in a polymer-stabilized blue-phase liquid crystal composite", Opt. Expr. 18, 11450 (2010). CrossRef K.A. Rutkowska, U.A. Laudyn, R.T. Rutkowski, M.A. Karpierz, T.R. Wolinski, J. Wójcik, "Nonlinear light propagation in photonic crystal fibers filled with nematic liquid crystals", Proc. SPIE 6582, 658215 (2007). CrossRef J. Li, C. Wen, S. Gauza, R. Lu, S. Wu, "Refractive indices of liquid crystals for display applications", J. Display Techn. 1, 51 (2005). CrossRef K. Rutkowska, A. Kozak, K. Orzechowski, "Chromatic dispersion measurements of selected liquid crystalline materials for integrated optics applications," Proc. SPIE (in press) (2016). E. Nowinowski-Kruszelnicki, J. Kędzierski, Z. Raszewski, L. Jaroszewicz, R. Dąbrowski, M. Kojdecki, W. Piecek, P. Perkowski, K. Garbat, M. Olifierczuk, "High birefringence liquid crystal mixtures for electro-optical devices", Optica Applicata 42, 167 (2012). DirectLink